Exploring the Implementation of Multimedia Technology in Contemporary Home Product Design for Regional Culture Inheritance and Innovation - Sheng, Kang (International Journal for Applied Information Management, 2023)
In recent years, the design market in China for household products has seen a surge in scale and speed. This shift has taken place from a decoration market to a design market. There is now a wide range of styles available for modern home product designs, with Western design styles becoming increasingly popular. However, it has been noticed that some domestic designers have followed the principles of modernism, minimalism, and high-techism, and this has resulted in many designs being created by simple copying of computer-generated designs, without much thought. This approach has led to the loss of the individuality of modern home product design styles. A modern household product design with an elegant taste and extraordinary style is not solely dependent on how much money is spent and how many high-grade decorative materials are used. It is important to combine regional culture with the appropriate use of the elements of modern household product design. It is also essential to create a fully functional, beautiful, generous, and elegant style for indoor environments with limited room space. Regional modern household product design refers to the combination of the local natural environment and cultural environment. It emphasizes local characteristics and national style, and the nationalization of modern household product design and creation tendency. In the design process, local materials and practices should be used as much as possible to display the characteristics of local conditions and merge the overall style with the local environment. To achieve this goal, it is essential to consider the region fully. Regional modern household product design can create a unique and individual design style. The use of local materials and practices will enable the design to reflect the characteristics of the local environment, resulting in a cohesive style. The use of regional culture and local elements will make the design more attractive to potential customers. Therefore, it is necessary to focus on creating a unique style of modern household product design, which combines regional culture with modern design elements.